The Potential of Green Belt Trees as Environmental Services for Emission Reduction in Banggae Timur, Majene Regency - Ritabulan; Rahman, Abd.; Qaizar; Abdullah, Muhammad Arafat; Irundu, Daud; Karim, Faradillah F. (Jurnal Hutan dan Masyarakat, 2025)
The issue of climate change is still a global concern today. Green belt trees as part of the ecosystem in urban areas in the context of environmental services have the ability to reduce emissions that cause global warming. This research aims to estimate the potential environmental services of tree-level vegetation to reduce carbon dioxide emissions in the East Banggae green belt area, Majene Regency. This research used a non-destructive sampling method with a total of 43 plots. Data analysis includes analysis of biomass, carbon and carbon dioxide potential as an approach to calculating the potential environmental services of East Banggae green belt trees. The research results show that based on the biomass and carbon potential of trees above ground, the East Banggae green belt trees contribute to reducing carbon dioxide emissions by 16,948.68 tons of CO2e per hectare.